Mobile application of the Terminology Subset for Coping with Domestic Violence Against Children - Mylene Gomes da Silva; Karen Namie Sakata-So; Érica Gomes Pereira; Emiko Yoshikawa Egry (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to describe the development of a mobile application for the International Classification Terminology Subset for Nursing Practice for Coping with Domestic Violence Against Children. Methods: an applied research of technological development, based on the Analysis, Design, Development, Implementation and Evaluation model and on the terminological subset based on the Theory of Nursing Praxis Intervention in Collective Health framework. Results: the application is divided into: 1) "Definition": characterizes the phenomenon of violence against children; 2) "Assistance": electronic record of nursing care; 3) "Diagnosis Consultation"; 4) "Intervention Consultation": nursing diagnoses, outcomes, and interventions related to children and their families, subdivided into Strengthening and Weariness group. Final considerations: built from scientific research, the application has the potential to support nursing care, presenting, in an organized and systematic manner, nursing diagnoses, outcomes, and interventions, in addition to enabling the registration of cases under monitoring.